Role of Electronic Records and Video Conferencing in Accelerating Summary Trials Under Bnss, 2023 (Journal of Advances and Scholarly Researches in Allied Education, 2026)
The Bharatiya Nagarik Suraksha Sanhita, 2023 (BNSS) marks a decisive shift in India’s criminal procedure by mainstreaming audio-video electronic processes and digital records across investigation, inquiry, and trial. Read together with the Bharatiya Sakshya Adhiniyam, 2023 (BSA), which elevates many electronic records to the status of primary evidence, these reforms are poised to compress timelines and reduce friction in summary trials—the forum intended for swift resolution of less complex cases. This article critically examines how (i) e-summons and other electronic communications, (ii) examination of accused and witnesses via live link/video conferencing (VC), and (iii) presumptions and custody rules for digital evidence can shorten case cycles without diluting due-process. It traces the doctrinal roots from State of Maharashtra v. Praful B. Desai (2003) through the Supreme Court e-Committee’s Model VC Rules (2020), before unpacking BNSS provisions on summary trials (chs. XXII; ss. 283–288), e-service of summons (ss. 63–71), recording by audio-video means in investigation and trial, and allied rules. Comparative vignettes from the UK, US, and Singapore show that speed gains from VC and e-evidence are real but contingent on consent, courtroom control, digital divide safeguards, and calibrated use (especially for vulnerable witnesses). The piece concludes with a workload-sensitive roadmap: standard operating procedures for e-summons, authenticated VC hubs at police stations/courts, bench-bar training, and privacy-security baselines. Properly implemented, BNSS + BSA can convert summary trials into a genuinely time-bound, digital-first track while keeping the fairness compass steady.